Monitoring Seismic Velocity Changes Across the San Jacinto Fault Using Train‐Generated Seismic Tremors. Issue 19 (30th September 2022) - Sheng, Y.; Mordret, A.; Sager, K.; Brenguier, F.; Boué, P.; Rousset, B.; Vernon, F.; Higueret, Q.; Ben‐Zion, Y.
Abstract: Microseismic noise has been used for seismic velocity monitoring. However, such signals are dominated by low‐frequency surface waves that are not ideal for detecting changes associated with small tectonic processes. Here we show that it is possible to extract stable, high‐frequency body waves using seismic tremors generated by freight trains. Such body waves allow us to focus on small velocity perturbations in the crust with high spatial resolution. We report on 10 years of seismic velocity temporal changes at the San Jacinto Fault. We observe and map a two‐month‐long episode of velocity changes with complex spatial distribution and interpret the velocity perturbation as produced by a previously undocumented slow‐slip event. We verify the hypothesis through numerical simulations and locate this event along a fault segment believed to be locked. Such a slow‐slip event stresses its surroundings and may trigger a major earthquake on a fault section approaching failure. Plain Language Summary: We turn seismic noise generated by freight trains into repeatable measurements of body waves that dive through the core of the San Jacinto Fault zone, CA. These body waves, which are typically hard to extract with standard approaches, are used to continuously monitor seismic velocity changes potentially associated with fault movements. During the 10‐year monitoring period, we observe a 2‐month‐long velocity perturbation in 2014 near the Anza seismic gap. We interpret this seismic velocity change as the result of a previously unknown slow‐slip event that occurred at the southern end of the seismic gap, at the transition to the very seismically active area. This slow‐slip event is below the geodetic detection threshold but increases the seismic stress in the seismic gap large enough to possibly trigger a big earthquake. Key Points: We extract stable station‐station body‐wave correlation functions using seismic energy generated by freight trains We perform 10‐year seismic velocity monitoring around the San Jacinto Fault and observe a 2‐month‐long velocity perturbation in 2014 We interpret this velocity change as caused by a previously unreported slow‐slip event at the southern edge of the Anza seismic gap